MEMPERLUAS MAKNA ZINA DALAM GUGATAN PERCERAIAN (Studi kasus putusan Pengadilan Agama Tigaraksa No. 1538/Pdt.G/2013/PA.Tgrs) - Sanjaya, Umar Haris (Universitas Borneo Tarakan, 2016)
Abstract This study focused on discussing the meaning of zina laws that existed at the Compilation of Islamic Law and Government Regulation No. 9 Year 1975 on the implementation of Law No. 1 Year 1974 on Marriage, which the courts in applying the word adultery should also look at the changing patterns of behavior and adultery today. Adultery should no longer be defined as sexual intercourse with the entry of male into the female sex, but the behavior of adultery was bermcam-wide one is oral sex. Behavior oral sex is a matter of a lawsuit against a husband and wife on the grounds of adultery lawsuit, but the court rejected it. This study contains the problem is how judges interpret the word adultery in making judgments in divorce? whether oral sex can be classified into the word adultery? The study found that oral sex by law can not be regarded as adultery, but the act of adultery into. Proof of adultery can only be recognized when the entity relationship entry into the male female sex. In conclusion, the judges interpret the meaning of the word adultery adultery per se, but the behavior of adultery are now widely different patterns and actions. Justice should not only look at the regulations simply make judgments, but look at the pattern of behavior or adultery committed in defining the word adultery.Keywords: adultery, oral sex, meaning law